Impact of unintentional weight loss on 30-day mortality in intensive care unit sepsis patients: a retrospective cohort study - Weide Lin; Bixia Lin; Junfan Chen; Renwei Li; Yaohua Yu; Shiqing Huang; Shurong Li; Jing Lin (Scientific Reports)
Abstract This study aimed to investigate the relationship between unintentional weight loss and 30-day mortality in sepsis patients in the intensive care unit (ICU). A retrospective cohort study sepsis patients in the ICU was conducted using data from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database, involving 1842 sepsis patients in the ICU. We utilized multivariate Cox regression analysis to evaluate the association between unintentional weight loss and the risk of 30-day mortality. In addition, we conducted stratified and interaction analyses to determine the consistency of this association across various demographic and clinical subgroups. Out of the 1842 patients, 19.2% (354) died within 30 days. The fully adjusted multivariate Cox regression model revealed that for every one-unit decrease in body weight, the risk of death increased by 58% (hazard ratio [HR] = 1.58; 95% confidence interval [CI] = 1.20–2.07). Unintentional weight loss was found to be positively correlated with 30-day mortality. Subgroup analysis yielded consistent results across all groups. Unintentional weight loss was positively associated with a greater risk of mortality in critically ill patients with sepsis in the ICU.